Aspergillus precipitating antibody in patients with Mycobacterium avium complex lung disease: A cross-sectional study. (May 2018) - Suzuki, Shoji; Asakura, Takanori; Namkoong, Ho; Okamori, Satoshi; Yagi, Kazuma; Kamata, Hirofumi; Uwamino, Yoshifumi; Funatsu, Yohei; Nakano, Yasushi; Nishimura, Tomoyasu; Ishii, Makoto; Ebihara, Tamotsu; et al.
Abstract: Rationale: Little is known about the role of Aspergillus precipitating antibody (APAb) in patients with Mycobacterium avium complex lung disease (MAC-LD). Objectives: We investigated the clinical characteristics of patients with MAC-LD positive for APAb. Methods: We conducted a cross-sectional study targeting patients with MAC-LD. APAb was checked in all participants. Clinical variables included laboratory data, pulmonary function, high-resolution computed tomography findings, and health-related quality of life. Results: We analyzed 109 consecutive patients. Their median age was 68 years, and the median duration of MAC-LD was 4.8 years. Twenty (18.3%) patients tested positive for APAb. APAb-positive patients had significantly longer duration of MAC-LD (9.4 vs. 4.0 years, P  = 0.017), more severe bronchiectasis evaluated by modified Reiff score (6.5 vs. 4, P  = 0.0049), and lower forced expiratory volume in 1 s (%FEV1 ) (75.1% vs. 86.2%, P  = 0.013) than APAb-negative patients. Analysis of covariance adjusted for background factors and underlying pulmonary disease revealed that %FEV1 was also significantly lower in patients with APAb ( P  = 0.045). Ten patients were newly diagnosed with chronic pulmonary aspergillosis (N = 5) or allergic bronchopulmonary aspergillosis (N = 5). Conclusions: APAb is associated with lower pulmonary function, and observed especially in patients with longer duration of MAC-LD and severe bronchiectasis, even in the absence of cavitary lesions. Highlights: 18% MAC-LD patients tested positive for Aspergillus precipitating antibody (APAb). APAb was observed in patients with severe bronchiectasis. APAb was associated with lower pulmonary function in MAC-LD patients. 9.2% of MAC-LD patients were newly diagnosed as CPA or ABPA.